Electrical resistivity-based approach to characterize moisture content in compressed earth bricks - Tuan Anh Nguyen; Minh Dung Pham; Wael Hafsa; Nicolas Angellier; Laurent Ulmet; Frédéric Dubois (Case Studies in Construction Materials)
Compressed earth bricks (CEBs) are increasingly used as a sustainable building material, but their hygroscopic nature makes them susceptible to moisture-related degradation. Monitoring moisture content in CEBs is crucial for ensuring structural integrity and durability, yet existing methods are often destructive or limited in application. This study presents a non-destructive approach for assessing moisture content in CEBs using electrical resistivity measurements, adapted from geophysical surveying techniques. The research employed a modified Syscal Junior Switch-48 resistivity meter with 4-electrode and 16-electrode configurations to measure electrical resistance in CEB samples under controlled relative humidity conditions ranging from 20 % to 100 %. Clear logarithmic correlations were established between moisture content (1.86–9.48 %) and electrical resistivity. The measured electrical resistivity varied from 12.4Ωm at 9.48 % moisture content to 3350Ωm at 1.86 % moisture content, demonstrating the method's sensitivity across a wide range of moisture levels. The 50 mA measurement mode demonstrated capability to assess moisture levels down to 1.86 %, while the standard 1250 mA mode was effective above 2.9 % moisture content. Numerical modeling using finite element analysis was conducted to determine geometric factors and true resistivity values. The 16-electrode multiplexed measurements showed good agreement with the experimental trend, enabling potential internal moisture mapping. This application of resistivity measurements represents a significant advance in non-destructive monitoring of earthen construction materials.